Against the leans: Overcoming spatial disorientation through galvanic vestibular stimulation. (September 2021) - Kim, Sungho; Jorella Lazaro, May; Jung, Hyunki; Hwan Yun, Myung; Kang, Yohan
Leans illusion is a type of Spatial Disorientation (SD) that pilots often experience which can adversely affect flight performance. For pilots' flight safety, research on how to effectively overcome SD such as leans illusion is important. The purpose of this study is to identify the overcoming effect of Galvanic Vestibular Stimulation (GVS) technology on leans illusion. Twenty-one Air Force pilots participated in a flight simulation experiment where leans illusion was induced through a specialized SD simulator. In the with-GVS condition, GVS was given during the roll-out phase. Data was analyzed using roll angle error and subjective SD scales by two conditions (with-GVS, without-GVS). Results showed that both the roll angle error and the subjective SD scale scores were found to be lower in the with-GVS condition than in the without-GVS condition. This study suggests that the use of GVS technology can potentially contribute in overcoming leans illusion.